Privatisierung der Strafverfolgung — Königsweg oder Irrweg? - Sieg, Rainer (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The comprehensive use of private individuals by the company management for the systematic clearance of suspected economic crimes has been for decades a tried and tested fact-finding method in the US legal system. In Germany this form of corporate private investigations took not place or was unknown to the public prosecution. This changed dramatically with the discovery of spectacular corruption affairs with international relation in 2007. “Internal Investigations” have developed since then to a lucrative commercial model particularly for American solicitor’s offices, because only these are accepted by the American authorities America only.However, the adherence to examination standards of a state under the rule of law must be also protected in the job. The judiciary must win back the inquiry sovereignty in the fight against economic crime.The fight against international economic crime can no longer be left to a single country alone. The fight against anti-competitive corruption should be a priority for the entire community. As an adequate means supplements to the Convention on the Fight against Corruption of the Council of the Organization for Economic Cooperation and Development OECD on the Laws of Transnational Criminal Prosecution of Economic Offenses come into consideration.
Keywords: prywatyzacja postępowań karnych; ściganie karne; dochodzenia prywatne; przestępstwa gospodarcze; korupcja; ściganie karne międzynarodowe